2015
DOI: 10.3389/fpsyg.2015.01335
|View full text |Cite
|
Sign up to set email alerts
|

The role of rumination in posttraumatic stress disorder and posttraumatic growth among adolescents after the wenchuan earthquake

Abstract: Three hundred and seventy-six middle school students in Wenchuan County were assessed three and one-half years after the Wenchuan earthquake to examine the effects of rumination on posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG). The results revealed that recent intrusive ruminations partly mediated the relationship between intrusive rumination soon after the earthquake with PTSD but not with PTG. Recent deliberate rumination partly mediated the relationship between intrusive rumination soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 53 publications
6
77
1
Order By: Relevance
“…Another interesting finding of this study was that intrusive rumination at T1 affect PTSD via intrusive rumination at T2 through deliberate rumination at T2, which are inconsistent with previous studies (Wu et al, 2015;Zhou et al, 2015b). A potential explanation may be difference on study design.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…Another interesting finding of this study was that intrusive rumination at T1 affect PTSD via intrusive rumination at T2 through deliberate rumination at T2, which are inconsistent with previous studies (Wu et al, 2015;Zhou et al, 2015b). A potential explanation may be difference on study design.…”
Section: Discussioncontrasting
confidence: 98%
“…More importantly, the results also showed that intrusive rumination at T1 had a significantly positive effect on PTSD at T3 by intrusive rumination at T2, which parallels the supposition from Michl et al (2013). It also indicated that if an adolescent's cognitive discrepancy in basic perceptions of personal worth, trust in others, and justice or predictability in the world, between pre-trauma and post-trauma cannot be resolved, the individual might continue to ruminate about it (Wu et al, 2015). As a result, traumatic survivors could focus on the negative aspect of traumatic clues, reduce the capacity to disengage attention from negative emotional information (Joormann, 2006), and encounter difficulties in generating good solutions to problems (Ward et al, 2003;Watkins and Moulds, 2005), which may also result in maintaining or worsening some symptoms of PTSD.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations